Perlindungan Hukum Pemilik Hak Cipta Terkait Pembajakan Karya Sinematografi Pada Platform Telegram - Bissil Mikafa, Alifia; R. Hariandja, Tioma; Hoiru Nail, Muhammad (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2022)
The cinematography in telegram is widely misused by irresponsible people by piracy. In fact, cinematography is a component contained in copyright law that must be protected. The first problem is how is the legal protection for copyright owners? And the second dispute resolution that can be taken by the copyright owner? This research method uses the normative method. And it will become a legal problem if piracy continues on Telegram. Copyright owners need to be protected with two forms of protection, namely preventive legal protection and repressive legal protection. As for dispute resolution, it can be done through litigation and non-litigation.